Reducing Cooling Energy Demand in Saudi Arabian Residential Buildings Using Passive Design Approaches - Lucelia Rodrigues; Benjamin Abraham Cherian; Serik Tokbolat (Buildings)
In Saudi Arabia’s hot and arid climate, residential buildings account for over half of national electricity consumption, with cooling demands alone responsible for more than 70% of this use. This paper explores the hypothesis that contemporary villa designs are inherently inefficient and that current building regulations fall short of enabling adequate thermal performance. This issue is expected to become increasingly significant in the near future as external temperatures continue to rise. The study aims to assess whether passive design strategies rooted in both engineering and architectural principles can offer substantial reductions in cooling energy demand under current and future climatic conditions. A typical detached villa was simulated using IES-VE to test a range of passive measures, including optimized window-to-wall ratios, enhanced glazing configurations, varied envelope constructions, solar shading devices, and wind-tower-based natural ventilation. Parametric simulations were conducted under current climate data and extended to future weather scenarios. Unlike many prior studies, this work integrates these strategies holistically and evaluates their combined impact, rather than in isolation while assessing the impact of future weather in the region. The findings revealed that individual measures such as insulated ceilings and reduced window-to-wall ratios significantly lowered cooling loads. When applied in combination, these strategies achieved a 68% reduction in cooling energy use compared to the base-case villa. While full passive performance year-round remains unfeasible in such extreme conditions, the study demonstrates a clear pathway toward energy-efficient housing in the Gulf region.